2016
DOI: 10.1016/j.bpj.2016.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Regulation of Three-Dimensional Epithelial Fold Pattern Formation in the Mouse Oviduct

Abstract: Epithelia exhibit various three-dimensional morphologies linked to organ function in animals. However, the mechanisms of three-dimensional morphogenesis remain elusive. The luminal epithelium of the mouse oviduct forms well-aligned straight folds along the longitudinal direction of the tubes. Disruption of the Celsr1 gene, a planar cell polarity-related gene, causes ectopically branched folds. Here, we evaluated the mechanical contributions of the epithelium to the fold pattern formation. In the mutant oviduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 45 publications
(87 reference statements)
1
56
0
Order By: Relevance
“…This model could also recapitulate the folding pattern in Celsr1-knockout mice by increasing the longitudinal length of the epithelium relative to its constraining cylinder. Adding support for this mechanical viewpoint, laser ablation experiments confirmed that the wild-type epithelium retracts more than the mutant in the longitudinal direction, indicating that the mutant is under lower longitudinal tension, as would be expected if the complex folds of the knockout were due to longitudinal compression of the epithelium [7]. This simple model can further recapitulate diverse and complex folding patterns by modifying the circumference and length of the epithelium relative to its constraining cylinder [7].…”
Section: Reproductive System (A) Oviductmentioning
confidence: 63%
See 1 more Smart Citation
“…This model could also recapitulate the folding pattern in Celsr1-knockout mice by increasing the longitudinal length of the epithelium relative to its constraining cylinder. Adding support for this mechanical viewpoint, laser ablation experiments confirmed that the wild-type epithelium retracts more than the mutant in the longitudinal direction, indicating that the mutant is under lower longitudinal tension, as would be expected if the complex folds of the knockout were due to longitudinal compression of the epithelium [7]. This simple model can further recapitulate diverse and complex folding patterns by modifying the circumference and length of the epithelium relative to its constraining cylinder [7].…”
Section: Reproductive System (A) Oviductmentioning
confidence: 63%
“…The adult mouse oviduct changes its shape and folding pattern during ovulation. Since the smooth muscle layer does not fold along with the epithelium, the circumferential length of the epithelium is greater than that of the smooth muscle, suggesting that the epithelial folds form through a buckling mechanism induced by the surrounding smooth muscle [7]. Knocking out the planar cell polarity gene Celsr1 leads to disordered alignment of epithelial cells, disordered folding in the longitudinal direction and the development of some circumferential folds.…”
Section: Reproductive System (A) Oviductmentioning
confidence: 99%
“…intestinal looping | buckling | biomechanics | Bmp | morphogenesis D ifferential growth represents one of the core physical mechanisms driving morphogenesis throughout the vertebrate embryo (1)(2)(3)(4)(5)(6)(7)(8)(9). Investigations into the mechanics of differential growth have often illustrated key physical parameters (e.g., tissue stiffness, growth rates, and initial geometry) that determine the resultant tissue shape.…”
mentioning
confidence: 99%
“…PCP is required to create a polarized network in which cells are elongated along the length of the tube; this allows for increased tissue-level tension along that axis, yielding well-aligned folds. Loss of Celsr1 abrogates cell elongation and reduces longitudinal tension, leading to misaligned folds [14, 15]. …”
Section: Morphogenesis Of 3d Tissue Architecture In Vivomentioning
confidence: 99%